2005
DOI: 10.1097/01.brs.0000160686.18321.ad
|View full text |Cite
|
Sign up to set email alerts
|

The Extent of Ossification of Posterior Longitudinal Ligament of the Spine Associated with Nucleotide Pyrophosphatase Gene and Leptin Receptor Gene Polymorphisms

Abstract: The present results suggest that the IVS20-11delT variant of the NPPS gene and the A861G variant of the leptin receptor gene are associated with more extensive OPLL, but not with the frequency with which it occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 20 publications
2
35
1
Order By: Relevance
“…However, the results of gene analysis studies are not always consistent. Involvement of many growth factors and cytokines, including bone morphogenic protein 2 (BMP2) and transforming growth factor-β (TGF-β) has been demonstrated in various histochemical and cytochemical analyses 6,10,14) . Several transcription factors involved in cellular differentiation may also have a role 4) .…”
Section: Resultsmentioning
confidence: 99%
“…However, the results of gene analysis studies are not always consistent. Involvement of many growth factors and cytokines, including bone morphogenic protein 2 (BMP2) and transforming growth factor-β (TGF-β) has been demonstrated in various histochemical and cytochemical analyses 6,10,14) . Several transcription factors involved in cellular differentiation may also have a role 4) .…”
Section: Resultsmentioning
confidence: 99%
“…Some evidence suggests that NPPS gene mutation is associated with OPLL development. 65,91 In a later study by Tahara et al, 114 the authors showed that NPPS and leptin receptor genes do not promote an increased susceptibility to OPLL, but are associated with the extent of heterotopic ossification. Horikoshi et al…”
Section: Pathogenesismentioning
confidence: 99%
“…Recent molecular genetic studies have identified several candidate genes that are differentially expressed in OPLL cells compared to normal ligament cells (15,16): reports suggest an increase in collagen, type VI, alpha 1 (Col6a1) (17,18); collagen type XI alpha 2 (Col11a2) (19,20); nucleotide pyrophosphatase (NPPS) (21 -24); leptin receptor (22); transforming growth factor-beta 1 (TGF-β1) (25 -27); promyelotic leukemia zinc finger (PLZF) (28,29); Tumor necrosis factor-alpha-stimulated gene 6 (TSG-6) (29); connective tissue growth factor (CTGF) (12); prostaglandin I 2 (PGI 2 ) (13) and endothelin-1 (30), amongst others. However, thus far, genetic factors have not been statistically linked to DISH or OPLL, most likely owing to the complexity of these diseases.…”
Section: Introductionmentioning
confidence: 99%